Analisa Performa Sistem Berkas Ext4 Pada Kondisi Tervirtualisasi - Salman Farizy; Tommy Gunawan (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2020)
Various file system that created and used by computer and operating system, so this journal is written for in depthlearning about one of the file system called ext4 on how they complete various task of file system using a benchmarkingprogram for unix in virtualized condition in virtual machine.